Heavy Metal Contamination in Soil at Waste Disposal Site and Surrounding Paddy Field Area in Khok Sa-At Subdistrict Administrative Organization, Khong Chai District, Kalasin Province - Kanchak, Angsuma; Passago, Somsanguan; Ponkham, Pornpimol; Trisupakitti, Somsuk (Burapha Science Journal, 2026)
The objective of this study was to examine the soil properties and heavy metals in the soil at the rice paddy fields surrounding the waste disposal site of Khok Sa-at Subdistrict Administrative Organization, Khong Chai District, Kalasin Province. The data collection involved collecting the soil samples from Spot A, B, and C. Spot A collected soil samples in the waste disposal site 25 meters away from the wall. Spot B and C collected soil samples in the rice fields surrounding the waste disposal site 2 meters and 20 meters away from the wall. Soil samples were collected from 6 spots in each area altogether 18 spots during August to November 2018. The soil properties were examined for pH, EC, and heavy metals by using Atomic Absorption Spectrophotometer Technique. The statistics for data analysis were mean and standard deviation. The results showed that Area A, B, and C showed pH at 5.59±0.01 – 8.32±0.01, 4.05±0.01 – 8.46±0.00, and 4.62±0.00 – 7.57±0.01 respectively. The EC mean was 12.72±0.04 – 195.47±0.06, 17.38±0.09 – 240.67±0.58, and 17.81±0.20 – 190.23±0.06 uS/cm. And, the heavy metals were in line with the standards prescribed by the Pollution Control Department except that of the lead in Spot A. The samples at Spot 3A detected lead at 1,208.87±0.15 mg/kg whereas the standard criteria prescribe not exceeding 400 mg/kg.